Retrospective Study of Cultural Arts Research in ASEAN - Mita Purbasari; Donna Carollina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Cultural arts are one of the important fields that studies human life activities. Cultural art being a human parameter is different from other creatures. So, research on cultural arts has developed and expanded over the centuries. Thus, the research departs from curiosity about the growing research trends in the field of cultural arts, especially in the ASEAN region. This study uses a bibliometric approach to see the research productivity of each country in the ASEAN region. So that it can be reviewed the development of research trends, especially in the last ten years in ASEAN countries. In addition, the results of the data analysis obtained will also be visualized using VOSviewer. This was done to see the clusters found related to cultural arts research in each ASEAN country. countries with many studies are significantly compared to countries with minimal research. The data used is sourced from the Scopus database. From the research carried out, it was found that countries with many studies are significantly compared to countries with minimal research. In addition, most of the documents are in the form of articles. In terms of clustering research themes, it was found that the results of visualizations that countries with many documents would produce a variety of research themes with diverse item relationships. So that there are still many research opportunities related to Cultural Arts that can be done by utilizing a variety of items resulting from clustering.